Active Control and Energy Cost Assessment of a Rotating Machine. (2011) - Mahfoud, Jarir; Skladanek, Yan; Der Hagopian, Johan
Abstract : The performances for controlling a rotating machine by using either an Electromagnetic Actuator or a Piezoelectric Actuator are compared in this work. The aim is to establish selection criteria based on environmental impact. Life Cycle Analysis shows that the operating stage has a considerable impact. In this study, only the operating stage is considered. The energy consumed by the actuators seems to be the appropriate indicator for the same "mechanical" performances. Numerical studies are carried out in order to quantify the energy consumed in each case. Modal control strategy with a fuzzy controller is used. The controller inputs are displacements and velocities. The system studied is modeled by using finite element method and the electrical circuit of each actuator is modeled by using basic electricity and electromagnetism theories. Several configurations are assessed and defined by using the chosen Functional Unit. The results obtained show that both controllers are efficient and enable recommendations for optimal control procedures design for the energy consumed.